Usulan kebijakan pencegahan risiko perbankan di era digital - Cahyolaksono, Bagaspati Atibrata; Mahardhika, Adhitya; Zakaria, Mochamad Ismail (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2021)
This study aims to provide appropriate policy proposals to strengthen the prevention of banking risks that can be considered by the OJK. Because nowadays, there are often cases of fraud that occur in banking, which makes customers become hesitant to choose banks to store their assets. The methodologies used in this study are literature studies and case studies. The cases used are fraud committed by the head of Maybank branch that provides losses reaching 20 billion rupiah and fraud of BRI customers who provide losses reaching 21 billion rupiah. This study shows two types of risks that arise in these two cases, namely operational risk and reputational risk. This study also produced some policy suggestions that can be considered for policy makers (OJK) to prevent similar fraud from happened again.